English vowel perception in L2 learners with Spanish as L1 - Bustos, José; Pereira, Yasna (Lenguas Modernas, 2020)
Research in the field of perception of second-language sounds (L2) has established that perceiving sounds in an L2 is difficult for learners, due to the phoneme inventory differences between one language and another (Akahane-Yamada, Tohkura, Bradlow & Pisoni, 2006). The objective of this study is to measure the auditory perception capacity of 11 English vowels (British accent) in 64 students from a school in Chillán, Chile. Two auditory perception tests were used: An Identification Test and a Discrimination Test. The study shows that the subjects obtained deficient results in both tests, which could suggest that the phonemic categories of the English vowels are still weak or non-existent in this group of subjects. In addition, it is observed that subjects could use their categories of Spanish as their mother tongue language (L1) to perceive some vowels of English (Best & Tyler, 2007; Gibson & Gibson, 1995).